Changes in in vitro protein digestion of retort‐pouched pork belly during 120‐day storage. (9th September 2017) - Zhou, Yiting; Yang, Wanjun; Zhou, Guanghong; Xu, Xinglian; Zhang, Zhigang; Ahmad, Muhammad Ijaz; Li, Chunbao
Summary: To investigate the effect of long‐term storage on in vitro protein digestion of the retort‐pouched pork belly. The products were stored at 25 °C for 0, 30, 60 and 120 days and digested with pepsin and trypsin at each time point. SDS‐PAGE and LC‐MS‐MS were applied to separate and identify proteins and their digested products. In vitro protein digestibility decreased from 47.7% after 60‐day storage to 25.4% after 120‐day storage for the samples digested by pepsin, and from 63.9% to 45.7% for the samples digested by pepsin and trypsin at corresponding time points. LC‐MS‐MS demonstrated changes in peptide composition and abundance with storage time. Long‐term storage could deteriorate nutritive values of meat products by reducing digestible protein content. Abstract : The products were stored at 25°C for different time and digested with pepsin and trypsin. SDS‐PAGE and LC‐MS‐MS were applied to separate and identify proteins and their digested products. In vitro protein digestibility decreased from during long‐term storage. Peptide composition and abundance in the digested products changed with storage time. Long‐time storage could deteriorate nutritive values of meat products by reducing digestible protein content.